Application of Weighted Sum Model (WSM) for Determining Development Priorities in Rural - Yuda Perwira; Wira Apriani (Jurnal Teknik Informatika C.I.T Medicom, 2020)
Currently, the government has received special attention to advance the economy and human resources of the village community through the regulation of the village minister, development of disadvantaged areas and transmigration of the Republic of Indonesia number 19 of 2017 concerning the prioritization of using village funds, therefore attention to supervising development in villages is very necessary to ensure that the development in the village is right on target and takes into account the priority needs of the village, as stated in Permendes Number 19 of 2017 CHAPTER II Article 3 concerning the determination of priority for the use of funds. The purpose of this research is to carry out the government's appeal on increasing community participation in the implementation and development of the village in accordance with the government's appeal for supervision of village funds as stipulated in Permendes Number 19 of 2017 so that development in villages prioritizes more urgent community interests and justice for all villagers without distinction. -different, a decision support system is needed to support this activity to be better and more efficient.The stages of the method in the research are direct field visits, namely the village of Jati Baru, kecamatan merbau, Deli Serdang Regency, North Sumatra, conducting interviews with the village head, village officials and local villagers in order to obtain information related to this research then look for references and literature studies through research journals, laws, government regulations, and other matters relevant to this research, then apply the Weigthed Sum method. The model is a method of solving problems, designing systems, building systems, testing systems and implementing a decision support system for determining development priorities in Jati Baru Village, Pagar Merbau District, Deli Serdang Regency, North Sumatra. The results of this study are the decision support system for determining development priorities in the village and the system is proven to be able to solve the problem of determining development priorities in the village based on predetermined alternatives and criteria.